PENGARUH MEDIA EDUKASI BOOKLET GIZI SEIMBANG BALITA DENGAN PEMANFAATAN PANGAN LOKAL TERHADAP PENINGKATAN PENGETAHUAN KADER (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Nutritional status is one of the important factors in achieving optimal health status. Under the Red Line Nutritional Status in Kalipucang District 109 children under five are vulnerable aged 12-59 months (Data from Kalipucang Health Center, 2022). Efforts to overcome this problem include providing information at the posyandu. Posyandu cadres are the main driver of all activities carried out at posyandu. Increased knowledge can be done with health education through health promotion media. One of the media that is often used in health education is a booklet. Objective: To determine the effect of education through booklet media on the knowledge of posyandu nutrition cadres regarding balanced nutrition for toddlers with the use of local food. Methods: This study used a quasi-experimental design with a one group pretest-posttest without control design. The sample of this study was 33. In this study, the instrument used to measure the respondent's knowledge variable was a questionnaire designed as a closed question in the form of True and False answer choices. Data analysis used the Wilcoxon signed test to prove the research hypothesis. Results: The average score of respondents' knowledge before being given a media booklet was 56.82. The average score of respondents' knowledge after being given a media booklet was 83.03. The percentage increase in knowledge was 26.21, the p value on the knowledge of respondents before and after being given a media booklet was (p = 0.001). Conclusion: There was a significant increase in knowledge after being given education through booklet media on the knowledge of posyandu nutrition cadres about balanced nutrition for toddlers with the use of local food. Recommendation: This research can be developed by further researchers regarding the effectiveness of booklet media in increasing knowledge compared to other types of media through appropriate administration to increase knowledge of optimal posyandu cadres. Keywords: booklet media, balanced nutrition of toddlers, posyandu cadres, knowledge, local food.